Compressed Filesystem for Managing Large Genome Collections - Marin-Caihuan, J (Oxford University Press, 2019)
Genome repositories are growing faster than our storage capacities, challenging our ability to store, transmit, process and analyze them. While genomes are not very compressible individually, those repositories usually contain myriads of genomes or genome reads of the same species, thereby creating opportunities for orders-of-magnitude compression by exploiting inter-genome similarities. A useful compression system, however, cannot be only usable for archival, but it must allow direct access to the sequences, ideally in transparent form so that applications do not need to be rewritten. Results: We present a highly compressed filesystem that specializes in storing large collections of genomes and reads. The system obtains orders-of-magnitude compression by using Relative Lempel-Ziv, which exploits the high similarities between genomes of the same species. The filesystem transparently stores the files in compressed form, intervening the system calls of the applications without the need to modify them. A client/server variant of the system stores the compressed files in a server, while the client s filesystem transparently retrieves and updates the data from the server. The data between client and server are also transferred in compressed form, which saves an order of magnitude network time. Availability and implementation: The C++ source code of our implementation is available for download in https://github.com/vsepulve/relz-fs. © 2019 The Author(s) 2019. Published by Oxford University Press. All rights reserved.